Genetic variation and phylogenetic relationships of Thelymitra javanica (Orchidaceae: Orchidoideae) in East and Central Java, Indonesia - I Made Saka Wijaya; Budi Setiadi Daryono; Purnomo (Society for Indonesian Biodiversity, 2020)
Abstract. Wijaya IMS, Daryono BS, Purnomo. 2020. Genetic variation and phylogenetic relationships of Thelymitra javanica Blume (Orchidaceae: Orchidoideae) in East and Central Java, Indonesia. Biodiversitas 21: 1174-1181. Thelymitra J.R. Forst & G. Forst is a terrestrial orchid genera and mainly distributed in Australia as a center of its diversification. Moreover, Thelymitra javanica Blume is the only species of Thelymitra found in Asia, especially in Indonesia. In Australia and New Zealand, most of Thelymitra species easily found in lowland, whereas, T. javanica in Indonesia preferred to grows near the peaks of mountains around 2,000-3,000 m asl. The high altitude correlated with high light intensity and lower soil nutrients which require specific adaptation of plant to survive. The wide range of adaptation could be due to the presence of genetic variability among populations of Thelymitra. Therefore, this study was carried out to assess the genetic variability and phylogenetic relationships of T. javanica in East and Central Java. The genetic variability of Thelymitra was evaluated by molecular approaches, which is preferably utilized to determine the plant taxonomy to establish the taxonomic uncertainties. ITS-nrDNA is a popular DNA marker that widely used in phylogenetic study among various taxa. Sequences were analyses using Maximum Likelihood method with 11 in-group, 6 interspecies out-group of Thelymitra, and 2 intergeneric out-group of Thelymitrinae subtribe. The result showed that ITS-nrDNA sequences of T. javanica have no variation in nucleotide compositions and showing polytomy branch in cladogram. Thelymitra javanica also has a close relationship with Thelymitra longifolia J.R. Forst & G. Forst that are endemic to New Zealand.